2023
DOI: 10.3389/fchem.2023.1141920
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the uptake of deuterated methionine in Drosophila with stimulated Raman scattering

Abstract: Introduction: Visualizing small individual biomolecules at subcellular resolution in live cells and tissues can provide valuable insights into metabolic activity in heterogeneous cells, but is challenging.Methods: Here, we used stimulated Raman scattering (SRS) microscopy to image deuterated methionine (d-Met) incorporated into Drosophila tissues in vivo.Results: Our results demonstrate that SRS can detect a range of previously uncharacterized cell-to-cell differences in d-Met distribution within a tissue at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…29 Spratt et al demonstrated the visualization of deuterated methionine incorporated into the Drosophila tissue in vivo. 31 These applications collectively verified the qualitative capability of SRS microscopy in investigating protein and amino acid metabolism in cells and tissues both in vitro and in vivo. Furthermore, SRS microscopy has shown its capability in rapid antimicrobial susceptibility testing by measuring deuterium oxide (D 2 O) metabolic incorporation at the single-bacterium level.…”
Section: ■ Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…29 Spratt et al demonstrated the visualization of deuterated methionine incorporated into the Drosophila tissue in vivo. 31 These applications collectively verified the qualitative capability of SRS microscopy in investigating protein and amino acid metabolism in cells and tissues both in vitro and in vivo. Furthermore, SRS microscopy has shown its capability in rapid antimicrobial susceptibility testing by measuring deuterium oxide (D 2 O) metabolic incorporation at the single-bacterium level.…”
Section: ■ Introductionmentioning
confidence: 65%
“…It has demonstrated its great potential in visualizing protein and amino acid metabolism by combining with deuterium labeling in previous studies. Specifically, Wei et al reported that deuterium amino acids are generally nonperturbative to live cells and can be used for spatial mapping of newly synthesized proteomes in cells and tissues. , Miao and Wei showed that deuterium-labeled glutamine enables imaging of protein aggregation in Huntington’s disease . Spratt et al demonstrated the visualization of deuterated methionine incorporated into the Drosophila tissue in vivo . These applications collectively verified the qualitative capability of SRS microscopy in investigating protein and amino acid metabolism in cells and tissues both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 91%
“…This discrepancy likely arises from the enhanced and minimally invasive uptake kinetics of d8-Met compared to Hpg, as well as the nearly natural labeling afforded by deuterium. Additionally, we demonstrate SRS imaging to visualize d8-Met in multiple dissected Drosophila tissues incorporated systemically in vivo 33 . Utilizing our integrated SRS and fluorescence microscope, we were able to observe specific cells and investigate the heterogeneous nature of cells within tissues at subcellular resolution, revealing variations in d8-Met uptake and distribution among different cells.…”
Section: Introductionmentioning
confidence: 99%
“…Raman imaging technique has unveiled the biological behaviors of medicines and biomolecules labelled with cyano groups, alkynyl groups, and deuterium atoms. 6 The 1900–2400 cm −1 chromophores have also been used in biomolecular IR studies including those using femtosecond measurements. 7 VCD technique should also be benefited by the 1900–2400 cm −1 region such as its application to structural analysis of bigger (bio)molecules.…”
Section: Introductionmentioning
confidence: 99%